KEABSAHAN TANDA TANGAN ELEKTRONIK PADA PERJANJIAN JUAL BELI BARANG DARI PERSPEKTIF HUKUM PERDATA - Thamaroni Usman (Faculty of Law, Universitas Lampung, 2020)
Electronic transaction agreement between PT. Juang Abadi Alam with Australian Rural Exports Pty. Ltd in the perspective of the ITE Law is legal and has consequences. In another perspective, Article 1320 of the Civil Code sees that an agreement will be valid when two conditions are fulfilled, namely subjective and objective conditions. The focus of this study is related to the validity of the digital signature (scanner) of an agreement in the perspective of civil law as well as the legal consequences of the agreement carried out online / electronically when one party defaults/breach of contract. The legal research method used in this study is normative juridical.The results of this study showed that the process of electronic commerce transactions (e-commerce) is carried out with 4 stages of the agreement theory namely supply, acceptance, payment and delivery. The validity of agreement with digital signatures in the perspective of civil law is referring to the National Electronic Transaction Information law and Government Regulations as implementing regulations of Electronic Transactions, which are associated with the principles of agreement in the Civil Code. In addition, the legal consequences of an agreement made online/electronically when one of the parties to the default/breach of contract is that a cancellation of the agreement can be requested from the judge as a legal consequence or the legal consequences of the contract in the sale and purchase agreement of goods online.